Saint-Pierre d’Orbais - Killian, Kyle (Brepols, 2025)
The fragmentary remains of the Benedictine monastery of Saint-Pierre d'Orbais in northwest Champagne preserves a particular iteration of Gothic style and technological achievement as well as the built environment of a community deeply embedded in the world around them. Through their architecture, successive generations of monks of Orbais, whose institutional life stretched from the end of the seventh century to end of the eighteenth century, were constantly seeking to clarify their position in the changing physical and social landscapes they inhabited. Although connected by a shared site, the architectural evidence from Orbais preserves remnants from several episodes of use and reuse. The site is treated thematically, starting with the boundaries that define the site, then the resources that shaped monastic life in this particular location, followed by the monastic landscapes that shaped the community as an institution. These categories reflect both the nature of our evidence for the contexts of building construction and the types of landscapes that were most active for the monastic community at Orbais over the long life of the site. The final chapter resituates the architectural history of the monastic church in light of these interrelated landscapes, contextualizing existing scholarship that treats it as a specifically Gothic monument, and providing lines of connection to medieval built environments more broadly.